Torque - Moritz, Neal H.; Luff, Brad.; Johnson, Matt.; Kahn, Joseph; Henderson, Martin, 1974-; Ice Cube (Musician); Mazur, Monť, 1976-; Scott, Adam, 1973-; Schulze, Matt.; Lee, Will Yun, 1975-; Pressly, Jaime, 1977-; Bessley, Max, 1971-; et al. (Burbank, CA : Warner Home Video, 2004)
Biker Cary Ford is framed by an old rival and biker gang leader for the murder of another gang member who happens to be the brother of Trey, leader of the most feared biker gang in the country. Ford is now on the run trying to clear his name from the murder, while Trey and his gang are on the look out for his blood.
Special features: 2 pedal-to-medal commentaries by the stars and filmmakers; animated storyboards of racing and train-stunt sequences; Youngbloodz "Lean low" music video.
Director of photography, Peter Levy ; editors, Howard E. Smith, David Blackburn ; music, Trevor Rabin ; costume designer, Elisabetta Beraldo ; production designer, Peter J. Hampton ; visual effects supervisor, Eric Durst.
Martin Henderson, Ice Cube, Monet Mazur, Adam Scott, Matt Schulze, Will Yun Lee, Jaime Pressly, Max Bessley, Christina Milian, Jay Hernandez.
MPAA rating: PG-13; for violence, sexuality, language and drug references.
DVD, Region 1, widescreen (2.40:1) presentation; Dolby Digital, DTS, SDDS, dual-layer.
English or dubbed French dialogue, French or Spanish subtitles; closed-captioned.
Keywords: Motorcycle gangs -- Drama; Revenge -- Drama; Venganza -- Teatro; Feature films; Motorcycle films; Video recordings for the hearing impaired